2022
DOI: 10.3389/fimmu.2022.954391
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation as a consequence of SARS-CoV-2 infection

Abstract: Erroneous immune responses in COVID-19 could have detrimental effects, which makes investigation of immune network underlying COVID-19 pathogenesis a requisite. This study aimed to investigate COVID-19 related alterations within the frame of innate and adaptive immunity. Thirty-four patients clinically diagnosed with mild, moderate and severe COVID-19 disease were enrolled in this study. Decreased ILC1 and increased ILC2 subsets were detected in mild and moderate patients compared to healthy controls. NK cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Contrary to a previous study that demonstrated the deletion of ORF8 in AS resulted in higher concentrations of IFN-γ and lower concentrations of chemokines IP-10 (CXCL10), MCP-1 (CCL2), and MIP-1β (CCL4) [ 11 ], our research discovered that plasma IL-10, IL-17A, and IL-8 levels were higher in ∆871 BA.2 infected adult patients compared to BA.2 infected adult patients. Multiple studies have shown that IL-10, IL-17A, and IL-8 levels positively correlate with clinical severity in SARS-CoV-2-infected patients [ 25 ]. Therefore, we hypothesize that the observed difference may be related to the higher rate of asymptomatic infection in WT BA.2 breakthrough infected patients compared to ∆871 BA.2 breakthrough infected patients (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to a previous study that demonstrated the deletion of ORF8 in AS resulted in higher concentrations of IFN-γ and lower concentrations of chemokines IP-10 (CXCL10), MCP-1 (CCL2), and MIP-1β (CCL4) [ 11 ], our research discovered that plasma IL-10, IL-17A, and IL-8 levels were higher in ∆871 BA.2 infected adult patients compared to BA.2 infected adult patients. Multiple studies have shown that IL-10, IL-17A, and IL-8 levels positively correlate with clinical severity in SARS-CoV-2-infected patients [ 25 ]. Therefore, we hypothesize that the observed difference may be related to the higher rate of asymptomatic infection in WT BA.2 breakthrough infected patients compared to ∆871 BA.2 breakthrough infected patients (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the C-Vx application might be more successful in the mild and moderate stages of the disease. In a recent study of our group including mild, moderate, and severe patients, increased anti-inflammatory but decreased inflammatory responses were correlated with disease severity [ 36 ]. Supporting these results, the correlation analysis in this study demonstrated more positive or negative correlations in the Th2 direction without C-Vx, which increase from mild to severe phase.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MS) is a disease characterized by insulin resistance, hypertension, dyslipidemia and an increase in body mass index [1]. An essential factor in development of this disease is the rise in the consumption of high-calorie, low-fiber fast food as well as the decline in physical activity [2].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, excessive fructose consumption has become an important factor in development of metabolic syndrome, as it can cause an increase in blood pressure and triglycerides as well as insulin resistance [5]. In addition, it has been reported that an experimental metabolic syndrome model can be created in rodents with high fructose intake [1]. The metabolic syndrome induced by feeding with a high fructose or fatty diet causes various degrees of damage such as irregularity in microvilli [5], epithelial swelling, epithelial degeneration, villus collapse and chronic inflammatory cell infiltration in small intestine [6].…”
Section: Introductionmentioning
confidence: 99%